Public Awareness of Alzheimer’s Disease: A Cross-Sectional Study from Saudi Arabia - Alorfi NM (International Journal of General Medicine, 2022)
Nasser M Alorfi Department of Pharmacology and Toxicology, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi ArabiaCorrespondence: Nasser M Alorfi, Department of Pharmacology and Toxicology, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia, Tel +966500644261, Email nmorfi@uqu.edu.saBackground: Alzheimer’s disease is considered the most common neurodegenerative and progressive illness. It is also a common type of dementia characterized by brain atrophy, neuronal tissue loss, and the formation of amyloid plaques. Mild memory loss is a commonly expected start of the disease, which can progress to loss of capacity to carry on a conversation and react to certain situations.Objective: This study aimed to measure knowledge about Alzheimer’s disease in Saudi Arabia through the use of the Alzheimer’s Disease Knowledge Scale (ADKS) and measure the association between the ADKS with relevant demographic variables.Methods: A pre-validated questionnaire containing 30 questions was distributed electronically to anyone older than 18 years old living in Saudi Arabia. Items regarding socio-demographic characteristics and the Alzheimer’s Disease Knowledge Scale (ADKS) were also included.Results: Participants did not have a high enough mean score to be regarded as appropriately knowledgeable (mean = 17.35). Higher knowledge scores on Life impact, Risk factors, Assessment and diagnosis, Caregiving, Treatment and management, and ADKS were associated with the female gender. Higher knowledge of caregiving was associated with a postgraduate academic qualification. Higher knowledge on Assessment and Diagnosis was associated with higher age. Higher knowledge on risk factors was associated with having relatives diagnosed with Alzheimer’s disease. Higher knowledge on life impact was associated with having newspaper and journal articles as the source of medical information.Conclusion: National awareness campaigns for the community and continuing education courses for caregivers must be placed to aid in increasing awareness regarding Alzheimer’s disease.Keywords: Alzheimer’s, dementia, neurodegenerative diseases, knowledge, awareness